Pharmacokinetics of prednisolone in children: an open-label, randomised, two-treatment cross-over trial investigating the bioequivalence of different prednisolone formulations in children with airway disease. Issue 1 (26th September 2019) - Haslund-Krog, Sissel Sundell; Schmidt, Maria; Mathot, Ron; Kryger Jensen, Andreas; Jørgensen, Inger Merete; Holst, Helle
Abstract : Introduction: One in three Danish children under 3 years of age experience asthma-like symptoms, and one-third will later be diagnosed with asthma. Oral prednisolone is used in various formulations to treat acute asthma. However, the potential differences in bioequivalence between these formulations have never been examined in children despite interchangeable use in clinical practice. Methods and analysis: An open-label, randomised, two-treatment cross-over trial investigating the bioequivalence of different prednisolone formulations in children with airway disease. The included patients (6 months–11 years of age) are admitted to the Department of Paediatric and Adolescent Medicine Nordsjællands University Hospital, Hillerød, with asthma or asthma-like symptoms. The primary objective is to assess the bioequivalence between different prednisolone formulations herein area under the concentration time curve, Cmax and Tmax using saliva samples. The secondary objectives are to evaluate tolerability (five-point face scale), adverse events and severity of the disease. If the patient has an intravenous access for other purposes, the saliva samples will be validated with plasma samples. A total of 66 evaluable patients are needed according to European Medicines Agency Guideline on bioequivalence. Ethics and dissemination: Traditional pharmacokinetic trials are burdensome due to the extent of blood samples necessary to capture the time-dependant drug profile. Saliva sampling is far more acceptable for paediatric patients. In addition, this trial adheres to standard dosing strategies. No additional venepunctures are performed, and no additional prednisolone doses are administered. Guidelines for paediatric bioequivalence trials are warranted. Trial registration number: The Danish Medicines Agency EudraCT: 2017-003590-33, The Ethics Committee case no: H-17027252, and the Danish Data Protection Agency: BFH-2017–103, I-Suite no.: 05935.